Familia y escuela: estudio de la discapacidad desde la inclusión y la equidad - Quiroz Villacís, Jenny Andrea (2018)
Achieve a greater approach of the family to school. The educational community cannot be conceived without the active incorporation of parents. The participation of parents is undoubtedly a right but also a duty. This originates the investigation and analysis of this discourse to describe the elements that intervene there; it is a research of qualitative approach, Hermeneutical method. The results of the investigation showed that the role of the family is determinant in the school success, and in the life itself of the child with disability, since it emphasizes that a fundamental pillar for equity, communication between the school and the family. According to the findings, the importance of an educational vision that transcends the strictly educational and becomes a fundamental tool for the transformation of the life of children with disabilities, highlighting the scope and value as an epicenter for the formation of a new society the integration between the school and the family that projects a true inclusion with equity.